Pacientes transplantados renais com função renal estável: estudo de biomarcadores inflamatórios/ hemostáticos e relação com a função renal e o tempo pós-transplante - Ana Paula Lucas Mota (2012)
Kidney transplantation is a best treatment option for chronic renal disease in dialysis stage.This process is associated with improved quality of life and longer survival of patients with end stage renal disease compared to dialysis. Renal transplant is able to trigger an intense inflammatory response and alterations in the hemostatic system. However the pathophysiological mechanisms leading to these changes are not completely understood. The aim of this study was to investigate inflammatory and hemostatic biomarkers in patients undergoing renal transplant according to renal function and post-transplant time without clinical signs of rejection. We evaluated the plasma levels of regulatory (IL-4, IL-5 e IL-10) and proinflammatory cytokines (IL-8, IL-6, IL-1â, TNF-á, IL-12p70, IFN-) by flow cytometry and hemostatic parameters (thrombomodulin/TM, von Willebrand factor/FvW, ADAMTS13 and D dimer/D-Di) by ELISA. The patients were classified into subgroups according to creatinine plasma levels (C1:<1.4mg/dL; C2:1.4-2.0mg/dL e C3:>2.0mg/dL) and time post transplant (T1:1-24 months; T2:25-60 months; T3:61-120 months e T4: >120 months). Results showed an increase of D-Di and tendency to increase of IL-6 levels in the subgroup C3 compared to C1. Higher levels of IL-5 were obtained in the subgroup T1 compared to T2 as well as high levels of IL-12 were obtained in T4 when compared to T3. Multinomial regression analysis revealed that ADAMTS13 was associated with creatinine plasma levels. A multivariate logistic regression analysis showed that the female, subgroup T3 and Di-D levels were associated with glomerular filtration rate. These results suggest that the D-Di was a promising marker to estimate renal function. Moreover, the regulation of inflammation in the short term was mediated by IL-5 and the pro-inflammatory state in the long was mediated by IL-12. Besides, ADAMTS13 has shown promise for estimating renal function; and female gender and post-transplant time "61-120 months" were associated with impairment of glomerular filtration rate